Familial Infantile Bilateral Striatal Necrosis - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2002)
The clinical and radiological evolution of familial infantile bilateral striatal necrosis (IBSN) was evaluated in 11 of 15 affected children born to consanguineous Israeli Bedouin parents and reported from the Schneider Children's Medical Center, Petah Tikva and Sackler School of Medicine, Tel Aviv University, and other centers in Israel.